Prevalence of hypertension and its association with psychosocial factors among old age home inmates in an urban area of Kancheepuram district, Tamil Nadu - V. M., Anantha Eashwar; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2017)
Background: Among the non-communicable diseases prevalent among old age home inmates, hypertension is one of the diseases which if not diagnosed and treated adequately, could lead to high mortality and morbidity due to limited resources. The objective of this study is to find out the prevalence of hypertension among the old age home inmates and also its association with psychosocial morbidity among them. Methods: This community based cross sectional descriptive study was done among 250 inmates of selected old age homes in Kancheepuram district. A total of 8 old age homes were randomly chosen and universal sampling was done in each old age home to obtain the required sample size. Structured questionnaire was used to collect data and psychosocial morbidity among the inmates was assessed by Depression, Anxiety and Stress scale (DASS 21). Data analysis was done by SPSS software version 21. Results: The prevalence of hypertension and prehypertension was found to be 72.8% and 10% respectively and the prevalence of psychosocial morbidity was found to be high among the study participants (depression– 68.4, anxiety–46.8, stress– 50.4). Statistically significant association was found between uncontrolled hypertension and psychosocial factors (anxiety and stress). About 27% of the hypertensive was unaware of free medication offered for hypertension at Government health centres. Conclusions: This study highlights the need for setting up of specialized geriatric clinics at Government Health Centres to provide speedy medical services and supply of medication for the elderly. Health education has to be given to both the inmates and care takers about chronic diseases like hypertension.